(1 - 3r + 3r2 - r3)S を考察する方法
多項式×等比型の和 バニシング(vanishing) 法 解説
S | = | 1・1 | + | 4・r | + | 9・r2 | + | 16・r3 | + | … | + | n2・rn-1 | ||||||
-3rS | = | - | 3・r | - | 12・r2 | - | 27・r3 | - | … | - | 3(n-1)2・rn-1 | - | 3n2・rn | |||||
3r2S | = | 3・r2 | + | 12・r3 | + | … | + | 3(n-2)2・rn-1 | + | 3(n-1)2・rn | + | 3n2・rn+1 | ||||||
-r3S | = | - | 1・r3 | - | … | - | (n-3)2・rn-1 | - | (n-2)2・rn | - | (n-1)2・rn+1 | - | n2・rn+2 | |||||
したがって, | ||||||||||||||||||
(1-3r+3r2-r3)S | = | 1 | + | r | + | vanishing | - | (n+1)2・rn | + | (3n2-(n-1)2)・rn+1 | - | n2・rn+2 |